Highly stable and uniformly dispersed 1T-MoS2 nanosheets co-induced by chemical pressure and 2D template method with high supercapacitor performance. Issue 13 (4th March 2022) - Li, Han; Lin, Shuai; Li, Hui; Wu, Ziqiang; Zhu, Lili; Li, Changdian; Zhu, Xuebin; Sun, Yuping
Abstract : A one-pot synthesis of a well-matched and high-stability 1T-M0.71 W0.29 S2 /Ti3 C2 T x MXene heterostructure with high supercapacitor performance. Abstract : Two-dimensional (2D) 1T-MoS2 with high conductivity and large layer spacing is considered as a superior electrode material for supercapacitors. However, the easy agglomeration and thermodynamical metastability characteristics of 1T-MoS2 nanosheets restrict its electrochemical performance and wide application. It is a challenge to obtain highly stable and uniformly dispersed 1T-MoS2 nanosheets by a simple method. Herein, a high-stability 1T-MoS2 induced by W doping is obtained, which uniformly grows in situ on the surface of a 2D Ti3 C2 T x MXene template, by a one-pot hydrothermal synthesis. The microstrain introduced by accurately controlling W doping (29 at%) induces the phase transformation of 1T-MoS2, and the appropriate amount of Ti3 C2 T x MXene provides an exact space for the uniform growth of 1T-MoS2, resulting in a well-matched 1T-Mo0.71 W0.29 S2 /Ti3 C2 T x MXene heterostructure. The components of the above heterostructure take full advantage to their properties and help each other to achieve high structural stability and outstanding electrochemical performance as electrodes in a neutral electrolyte Na2 SO4 . Furthermore, the symmetrical devices fabricated with the well-matched 1T-Mo0.71 W0.29 S2 /Ti3 C2 T x heterostructure not only show high power and energy density but also outstanding flexibility and cycle stability. This study provides a simple method to achieve anti-aggregation and high-stability 1T-MoS2, and moreover, a new idea of using multiple methods at once for constructing high-performance 1T-MoS2 -based electrode materials.